Equivalence and translation strategies in multilingual thesaurus construction - Nykyri, Susanna (Åbo Akademi University Press, 2010)
Abstract.
Keywords: kääntäminen; tesaurukset; asiasanastot; översättning (verksamhet); tesaurusar; ämnesordsregister